A fast nonlinear dynamic analysis automated approach to produce fragility curves for 3D RC frames. (15th April 2023) - Nica, George-Bogdan; Pavel, Florin; Hojda, Gabriel
Highlights: The Matlab/Simulink capabilities are used in this paper with the scope of illustrating the claimed numerical efficiency of Force Analogy Method. The data produced to overcome the scopes of this paper reflects a set of 9600 full 3D nonlinear dynamic analyses. The risk assessment based on damage evaluation of structures is scarcely illustrated in the civil engineering literature. Abstract: This study describes an automated procedure to assess seismic fragility of 3D reinforced concrete frame structures. A number of 9600 3D nonlinear dynamic analyses are performed using the recently developed 3D Force Analogy Method, implemented in an automated Matlad-based non-commercial code. The numerical efficiency of 3D Force Analogy is first illustrated for a broad range of structures and groud motion recordings and scaling factors. The ground motion dataset consisting of 20 horizontal recordings used in the study is characteristic for soft deep soil sites (e.g Bucharest) which are affected by large magnitude earthquakes originating in the Vrancea intermediate-depth seismic source. A total of 24 RC frame structures, both regular and irregular are employed in the study. The Park-Ang damage index is employed in order to evaluate the damage states of the structures. Fragility functions corresponding to life-safety and collapse damage states are obtained for both principal directions of the structures. The results show similar median fragility values on both principal directions, and a larger variability on the transversal direction. The analyses have also shown that the standard deviations evaluated for the mean annual failure rates corresponding to the two considered damage states and on both principal directions is almost equal to the mean value. The mean value of the collapse probability evaluated for the peak ground acceleration with a mean return period of 2475 years and based on the results of all 24 models is 6.1 % for the longitudinal direction and 6.5 % for the transversal direction.